Sensory Properties and Acceptability of Fermented Pearl Millet, a Climate-Resistant and Nutritious Grain, Among Consumers in the United States—A Pilot Study - May M. Cheung; Lauren Miller; Jonathan Deutsch; Rachel Sherman; Solomon H. Katz; Paul M. Wise (Foods)
Millets are climate-resistant, potential alternatives to wheat that could provide environmental, food security, and health benefits (e.g., lower glycemic index). However, millets are high in phytic acid, which reduces the bioavailability of essential minerals. Millets are often fermented in Africa and parts of Asia to improve bioavailability and, thus, nutritional value, but both unfermented and fermented millets may have flavors unfamiliar to Western cultures. We conducted two pilot studies on sensory perception and liking of whole grain, United States pearl millet (Pennisetum glaucum), in a group of U.S. consumers. In a preliminary study, we compared pearl millet treated under five different conditions (0, 48, and 96 h of fermentation fully submerged in either distilled water or in a 5% NaCl solution at 28 °C). We found that 96 h of spontaneous fermentation in water, an inexpensive and accessible technique consistent with consumer demand for minimally processed foods, reduced phytic acid by ~72%. However, consumers (n = 12) rated flatbreads made with fermented pearl millet as more bitter and sour than flatbreads made with unfermented pearl millet. In a second study, participants (n = 30) rated liking and purchase intent for whole wheat bread with 0 to 50% (w/w) substitution of pearl millet flour. Replacing up to 20% of wheat with fermented or unfermented pearl millet had no measurable effect on liking or purchase intent. More extensive substitution compromised liking, particularly with fermented pearl millet. More work is needed, but so far, there appear to be no sensory barriers to at least partial substitution of whole-grain pearl millet for wheat in whole wheat bread for United States consumers.